Prevention of mother-to-child HIV-1 transmission in Burkina Faso: evaluation of vertical transmission by PCR, molecular characterization of subtypes and determination of antiretroviral drugs resistance - Tani Sagna; Cyrille Bisseye; Tegewende R. Compaore; Therese S. Kagone; Florencia W. Djigma; Djeneba Ouermi; Catherine M. Pirkle; Moctar T. A. Zeba; Valerie J. T. Bazie; Zoenabo Douamba; Remy Moret; Virginio Pietra; et al. (Taylor & Francis Group, 2015)
Background: Vertical human immunodeficiency virus (HIV) transmission is a public health problem in Burkina Faso. The main objective of this study on the prevention of mother-to-child HIV-1 transmission was to determine the residual risk of HIV transmission in infants born to mothers receiving highly active antiretroviral therapy (HAART). Moreover, we detect HIV antiretroviral (ARV) drug resistance among mother-infant pairs and identify subtypes and circulating recombinant forms (CRF) in Burkina Faso. Design: In this study, 3,215 samples of pregnant women were analyzed for HIV using rapid tests. Vertical transmission was estimated by polymerase chain reaction in 6-month-old infants born to women who tested HIV positive. HIV-1 resistance to ARV, subtypes, and CRFs was determined through ViroSeq kit using the ABI PRISM 3,130 sequencer. Results: In this study, 12.26% (394/3,215) of the pregnant women were diagnosed HIV positive. There was 0.52% (2/388) overall vertical transmission of HIV, with rates of 1.75% (2/114) among mothers under prophylaxis and 0.00% (0/274) for those under HAART. Genetic mutations were also isolated that induce resistance to ARV such as M184V, Y115F, K103N, Y181C, V179E, and G190A. There were subtypes and CRF of HIV-1 present, the most common being: CRF06_CPX (58.8%), CRF02_AG (35.3%), and subtype G (5.9%). Conclusions: ARV drugs reduce the residual rate of HIV vertical transmission. However, the virus has developed resistance to ARV, which could limit future therapeutic options when treatment is needed. Resistance to ARV therefore requires a permanent interaction between researchers, physicians, and pharmacists, to strengthen the network of monitoring and surveillance of drug resistance in Burkina Faso.